2017
DOI: 10.1093/humrep/dex033
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thyroid autoimmunity in euthyroid women on live birth rate after IUI

Abstract: No external funding was used for this study. No conflicts of interest are declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 20 publications
3
55
1
2
Order By: Relevance
“…Since IUI theoretically exposes fertilized eggs to underlying autoimmune conditions in order to achieve gestation, we speculate that IUI is more likely to be affected by TAI than by ART. Only one previous report has evaluated the association between IUI and TAI [45]. It showed no relation between TPOAb positivity and pregnancy outcomes in women undergoing IUI, but TPOAb titers were not evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…Since IUI theoretically exposes fertilized eggs to underlying autoimmune conditions in order to achieve gestation, we speculate that IUI is more likely to be affected by TAI than by ART. Only one previous report has evaluated the association between IUI and TAI [45]. It showed no relation between TPOAb positivity and pregnancy outcomes in women undergoing IUI, but TPOAb titers were not evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…Thyroid autoimmunity is more common in women with infertility and recurrent pregnancy loss, and about a fifth of untreated antibody‐positive women develop an elevated TSH during the course of pregnancy indicating a degree of thyroid hormone deficiency. Observational studies have shown an increased risk of miscarriages, preterm birth and child neuro‐intellectual deficits in pregnant women with thyroid antibodies (TPOAb) although this association was not confirmed in some studies . However, the results of meta‐analyses support an overall increased risk of pregnancy loss in association with maternal thyroid autoimmunity in spontaneous as well as assisted pregnancies .…”
Section: Euthyroid Thyroid Autoimmunitymentioning
confidence: 98%
“…In a retrospective cohort study of 300 However, three studies reported no difference in ART outcomes between women with and without thyroid autoimmunity (46,47). In a retrospective cohort study of 3,143 euthyroid patients undergoing intrauterine insemination (IUI), among the 376 women who went on to conceive, Unuane et al reported no difference in live birth rates between TPOAb positive and TPOAb negative women, 86% (19/22) vs. 82% (201/354), respectively, OR 1.05, CI 0.76-1.47 (46). In a retrospective cohort study of 123 infertile, euthyroid women undergoing IVF or IVF with ICSI, 29 with thyroid autoimmunity and 94 without, Andrisani et al also reported no difference in implantation rates, 15 vs. 19%, P > 0.05 (exact cycle numbers not available), pregnancy rates, 29 vs. 34%, P > 0.05 (exact cycle numbers not available) or ongoing pregnancy rates, 26 vs. 31%, P > 0.05 (exact cycle numbers not available), although they did report significantly fewer grade 1 embryos collected in patients with antibody positivity, 22% (26/119) vs. 45% (176/394), P < 0.001 (47).…”
Section: C) Autoimmunity and Preterm Delivery (Question 19)mentioning
confidence: 98%
“…Based on the studies published since the 2017 ATA Guidelines, no alteration of the Guidelines are indicated, but further investigation is warranted. Five studies examined the association between thyroid autoimmunity and outcomes of ART (46)(47)(48)(49)(50). Two studies reported a negative association between thyroid autoimmunity and outcomes after ART (48)(49)(50).…”
Section: C) Autoimmunity and Preterm Delivery (Question 19)mentioning
confidence: 99%
See 1 more Smart Citation